The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Biochemical Toxicology - Heavy Metals and Nanomaterials 2020
DOI: 10.5772/intechopen.86213
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons (PAHs) and Their Influence to Some Aquatic Species

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants generated primarily during the incomplete combustion of organic materials (e.g., coal, oil, petrol, and wood). Many PAHs have toxic, mutagenic, and/or carcinogenic functions. PAHs are highly lipid soluble which lead to a fast absorption by the gastrointestinal tract of marine mammals. They are immediately distributed in a vast variety of tissues with a notable tendency for localization in body fat. Metabolism of PAHs is obtained vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 104 publications
0
18
0
Order By: Relevance
“…PAHs are highly lipid soluble and accumulate in body fat. PAHs are ubiquitous environmental contaminants that pose significant risk to the health of marine species [2].…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
“…PAHs are highly lipid soluble and accumulate in body fat. PAHs are ubiquitous environmental contaminants that pose significant risk to the health of marine species [2].…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%
“…In the marine environment, PAHs are usually adsorbed on small solid particles suspended, as well as on sediments, and thus they may enter the tissues of fish and other marine organisms through the food chain. However, whereas until 2007 the scientific community thought that the biomagnification and bioaccumulation processes, in edible marine organisms, can introduce PAHs in humans through the diet (Domingo et al 2007), it has recently been demonstrated (Baali and Yahyaoui 2019;Franco and Lavado 2019) that PAHs are quickly metabolised in fresh fish and do not accumulate in the muscle meat. In fact, due to the inducible enzymes of the cytochrome P450 family (Frasco and Guilhermino 2002), in particular CYP1A, that catalyse the addition of an oxygen atom to the PAH molecules, these last become highly polar conjugated metabolites that are then excreted into the urine or the bile for rapid elimination over the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer in fish and especially in benthic organisms in natural aquatic systems has also been reported. Baali and Yahyaoui [12] reported that benzo [a] pyrene leads to a decrease in weight and growth, an increase in the gonado-somatic index (GSI) in Japanese medaka (Oryzias latipes), and teratogenic effects on the heart of sardines (Clupea pallasii), zebrafish, and anemia in scorpion fish (Sebastes schlegelii).…”
Section: Introductionmentioning
confidence: 99%